Translation control of an immersed tunnel element using a multi-objective differential evolution algorithm. (April 2019) - Liao, Qing; Fan, Qin-Qin; Li, Jun-Jun
Highlight: Translation control problem of the immersed tunnel element is converted into a multi-objective optimization problem. A recently proposed multi-objective differential evolution algorithm is used. Obtained non-dominated solutions can assist decision-makers to adapt changing environment. Abstract: The translation of an immersed tunnel element under a water current flow is a typical optimization problem, which has been solved by various optimization approaches. Also, this problem is often addressed as a single objective optimization in most previous studies. However, the translation control of the immersed tunnel element often involves at least two conflicting objectives in actual situation. Therefore, converting the translation control problem of the immersed tunnel element into a multi-objective optimization problem is necessary and vital. Subsequently, a recently proposed multi-objective differential evolution algorithm is employed to solve this optimization problem. Results indicate that the multi-objective differential evolution algorithm can produce the most promising result when compared with other competitors, and provide a set of non-dominated solutions to assist decision-makers in completing the translation of the immersed tunnel element based on different targets and changing environment. Namely, the current study can help decision-makers to achieve a good trade-off among different objectives such as transport efficiency, transport cost, and transport safety in the translation control of the immersed tunnel element.